TRACHEAL ULTRASTRUCTURE OF PROTURA (INSECTA, APTERYGOTA) - Xue, L; Dallai, R; Yin, W (1993)
The tracheal systems of Sinentomon and Eosentomon (Apterygota : Protura) were examined in thin sections and compared with the tracheae of collembolan, Allacma. The tracheal system of Protura consists of spiracles and tracheae. The spiracle is a simple, concave cuticular cavity known as an atrium. A globular chamber is present between the atrium and trachea. The atrium of Eosentomon is decorated with ridges and has 2 small openings to tracheal recesses beside the central tracheal opening. The tracheae of Protura are characterized by a high frequency of taenidia and the absence of intima folds and intertaenidial spaces. The taenidia of Sinentomon have a rectangular section and those of Eosentomon are gable-shaped. The results also suggest that the tracheal recess of Eosentomon is a kind of stigmatic gland. The tracheal structure of Protura was compared with that of collembolans, insects, and other arthropods, and discussed in terms of phylogeny. © 1993.